2015
DOI: 10.1245/s10434-015-4613-1
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Lower Extremity Edema in Patients with Primary Endometrial Cancer

Abstract: LEE developed in more than one-third of patients with endometrial cancer after surgery, and LEE lasted for more than 12 months in most patients. A high number of dissected pelvic lymph nodes and postoperative radiotherapy is associated with LEE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
1
20
4
Order By: Relevance
“…In other studies the median number of removed lymph nodes is significantly higher, up to over 80 [20,27,28,31]. The number of removed lymph nodes seems to be of importance for developing LLL with an increasing risk for LLL when a larger number of lymph nodes are removed [10,21,22,24,[37][38][39][40][41][42]. Interestingly, and with no obvious reasonable pathophysiological explanation, Hareyama et al found a significantly lower risk of LLL in women when the number of removed lymph nodes exceeded 70 [28].…”
Section: Risk Factors For Lllmentioning
confidence: 92%
See 1 more Smart Citation
“…In other studies the median number of removed lymph nodes is significantly higher, up to over 80 [20,27,28,31]. The number of removed lymph nodes seems to be of importance for developing LLL with an increasing risk for LLL when a larger number of lymph nodes are removed [10,21,22,24,[37][38][39][40][41][42]. Interestingly, and with no obvious reasonable pathophysiological explanation, Hareyama et al found a significantly lower risk of LLL in women when the number of removed lymph nodes exceeded 70 [28].…”
Section: Risk Factors For Lllmentioning
confidence: 92%
“…Pelvic radiation therapy (RT) given alone or as adjuvant therapy after surgery has a varying impact on the development of LLL. In several studies RT has been shown to significantly increase the risk for LLL [9,10,16,21,23,24,34,37,40,44]. However, there are some studies that fail to demonstrate an association between RT and LLL [8,17,22].…”
Section: Risk Factors For Lllmentioning
confidence: 99%
“…In addition, the number of dissected pelvic lymph nodes is a risk factor for LEE. 20,25 Sentinel lymph node mapping may help in this regard because it is a relatively minimal invasive approach and associated with reduced morbidity. 6,27,28 It has been shown that SLNs are 3 times more likely to contain tumor cells than non-SLNs.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, lower extremity lymphedema after lymph node dissection is a primary cause of poor quality of life in patients with gynecologic cancer, and this adverse effect may require additional procedures or rehabilitation therapy. 7 To prevent unnecessary lymph node dissection, some authors have attempted to prove the oncological safety of omitting lymph node dissection in patients with a low risk of lymph node metastasis. In randomized trials, investigators have demonstrated that lymph node dissection in low-risk cancer patients does not improve recurrence-free survival (RFS).…”
mentioning
confidence: 99%